2020
DOI: 10.1159/000506683
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Infection Is a Risk Factor in Gastrointestinal Cancer: A Cross-Sectional and Meta-Analysis Study

Abstract: Background: This study was planned to investigate the association betweenhuman cytomegalovirus (HCMV) infection and gastrointestinal cancer (GIC) risk, by undertaking a meta-analysis and case-control cross-sectional study. Summary: A cross-sectional study analysis of 160 GIC patients and 100 control subjects indicated significantly higher HCMV prevalence in GIC patients based on the HCMV IgM test. However, a similar analysis based on an IgG test revealed no significant relationship. Further meta-analysis of 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 36 publications
(39 reference statements)
0
20
0
Order By: Relevance
“…In addition, the diverse HCMV genes in human cancers present different functional phenotypes in tumors. For example, Lv et al (24) reported that HCMV infection was associated with an increased gastrointestinal cancer risk. HCMV has a higher prevalence in patients with primary breast cancer and colorectal cancer with brain metastases, and the high expression of HCMV-immediateearly proteins (IE) in the tumor tissues of the patients suggests a poor prognosis (25).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the diverse HCMV genes in human cancers present different functional phenotypes in tumors. For example, Lv et al (24) reported that HCMV infection was associated with an increased gastrointestinal cancer risk. HCMV has a higher prevalence in patients with primary breast cancer and colorectal cancer with brain metastases, and the high expression of HCMV-immediateearly proteins (IE) in the tumor tissues of the patients suggests a poor prognosis (25).…”
Section: Discussionmentioning
confidence: 99%
“…The inverse association between CMV risk and small intestine cancer does not have a clear explanation. Several studies have suggested an association between CMV infection and an increased risk of colorectal cancer or gastrointestinal cancers overall 34–36 . In the general population, small intestine cancer is rare 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested an association between CMV infection and an increased risk of colorectal cancer or gastrointestinal cancers overall. [34][35][36] In the general population, small intestine cancer is rare. 37 Transplant recipients have an elevated risk of small intestine cancer, 3 which is unexplained.…”
Section: Discussionmentioning
confidence: 99%
“…HCMV has been shown to have oncogenic transforming potential in vitro. 16,37 In addition, HCMV has been studied as an oncomodulatory virus and is an important factor in prognosis and survival in immune compromised patients. Preventive/prophylactic methods have resulted in a considerable decrease in HCMV-related mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%